Chaos induced by weak A-coupled-expansion of non-autonomous discrete dynamical systems. Issue 11 (1st November 2016) - Zhang, Lijuan; Shi, Yuming; Shao, Hua; Huang, Qiuling
Abstract: This paper focuses on chaos induced by weak A -coupled-expansion of non-autonomous discrete systems in compact subsets of metric spaces and in bounded and closed subsets of complete metric spaces, separately. A new concept of weak A -coupled-expansion for non-autonomous discrete systems, whose condition is weaker than that of A -coupled-expansion, is introduced, and several new criteria of chaos induced by weak A -coupled-expansion of non-autonomous discrete systems are established. By applying some close relationships between chaotic dynamical behaviours of the original system and its induced systems, two criteria of chaos are established. One example is provided for illustration.